2010
DOI: 10.1051/0004-6361/200913510
|View full text |Cite
|
Sign up to set email alerts
|

Initial phases of massive star formation in high infrared extinction clouds

Abstract: Aims. The earliest phases of massive star formation are found in cold and dense infrared dark clouds (IRDCs). Since the detection method of IRDCs is very sensitive to the local properties of the background emission, we present here an alternative method to search for high column density in the Galactic plane by using infrared extinction maps. Using this method we find clouds between 1 and 5 kpc, of which many were missed by previous surveys. By studying the physical conditions of a subsample of these clouds, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
28
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 81 publications
(103 reference statements)
9
28
0
Order By: Relevance
“…A similar distribution was also found by Rygl et al (2010) using high-extinction clouds identified with Spitzer colour excess. Therefore it is reasonable to posit that AT-LASGAL typically traces the higher flux fraction of the Hi-GAL sources, although this depends on the intrinsic SEDs of the various objects.…”
Section: Global Properties Of the Galactic Structuresupporting
confidence: 82%
“…A similar distribution was also found by Rygl et al (2010) using high-extinction clouds identified with Spitzer colour excess. Therefore it is reasonable to posit that AT-LASGAL typically traces the higher flux fraction of the Hi-GAL sources, although this depends on the intrinsic SEDs of the various objects.…”
Section: Global Properties Of the Galactic Structuresupporting
confidence: 82%
“…4b) but its compact 70 μm emission is three times that of the flux predicted by the grey-body model that fits its cold envelope. This MDC also coincides with a 40 -beam water maser source (Rygl et al 2010) suggesting that it harbours an intermediateor high-mass protostar. The SiO emission at these two positions could easily originate from shocks within protostellar outflows because they are comparable to the weakest ones associated with IR-quiet MDCs in Cygnus X (Motte et al 2007 after distance correction).…”
Section: Are Protostars Responsible For the Sio Emission?supporting
confidence: 58%
“…We note that the dust opacities are likely to be uncertain by a factor of 2 (Ossenkopf & Henning 1994;Motte & André 2001). For comparison, Williams et al (2004), Enoch et al (2006), and Rygl et al (2010) used the same dust model as we did and interpolated the values of κ ν at 850 μm, 1.1 mm, and 1.2 mm to be 0.154, 0.114, and 0.1 m 2 kg −1 , respectively. These are slightly lower than our values, and the difference is likely to be caused by different extrapolation methods (e.g., log-interpolation) and/or different dust emissivity index, β, used by the authors to determine the value of κ ν ∝ ν β .…”
Section: Clump Masses Radii and H 2 Column And Number Densitiesmentioning
confidence: 99%